From Menger to Polanyi: The Institutional Way - Cangiani, Michele (Austrian Economics in Transition, 2010)
The crisis of the institutions of liberal capitalism dates back to the last decades of the nineteenth century. Economics was thenceforth forced to radically reconsider its achievements and even its basic presuppositions, to the extent that they were linked to a free-market and perfect-competition model.
Keywords: economic history; economic systems; economic theory; financial economics; history of economic thought; international economics; macroeconomics; mathematical methods; methodology; monetary economics; quantitative economics

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
Keywords: classical Greek economy; economic history; embeddedness